1998
DOI: 10.1046/j.1469-8137.1998.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Root proliferation, soil fauna and plant nitrogen capture from nutrient‐rich patches in soil

Abstract: We investigated interactions between plant roots, protozoa and nematodes after addition of patches containing inorganic or organic nitrogen in order to determine whether root proliferation could explain the capture of N by the plant from the patch. Decomposition of a "&N\"$C, dual-labelled, organic patch in the absence of plant roots was also examined. In the decomposing patch the amounts of "$C and "&N remaining co-varied and both declined with time. Nematode numbers increased. However, protozoan bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
138
9
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(163 citation statements)
references
References 55 publications
15
138
9
1
Order By: Relevance
“…4b). Repression of root growth in the presence of an organic patch has been demonstrated previously by Hodge et al (1998). Cui & Caldwell (1996) reported that proliferation of Agropyron desertorum roots in nutrient-rich patches decreased when colonized by AM fungi, although the difference was only weakly significant (P l 0.07).…”
Section: Root Proliferationmentioning
confidence: 79%
See 2 more Smart Citations
“…4b). Repression of root growth in the presence of an organic patch has been demonstrated previously by Hodge et al (1998). Cui & Caldwell (1996) reported that proliferation of Agropyron desertorum roots in nutrient-rich patches decreased when colonized by AM fungi, although the difference was only weakly significant (P l 0.07).…”
Section: Root Proliferationmentioning
confidence: 79%
“…Phosphorus contents of root and shoot tissues from the last two destructive harvests (30 and 41 d) were determined after a triple acid digestion and using the molybdenum blue method (Allen, 1974). Subsamples of the soil from the different sections of each tube were used for moisture content determinations (105mC) and for total C, N, "$C and "&N analysis (see Hodge et al, 1998).…”
Section: Plant and Soil Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This has been observed in the laboratory (Hodge et al, 1998), in natural ecosystems (Meier et al, 2009), and in many farming systems (Putnam, 1994). In a recent review of agricultural applications of organic matter, Bonanomi et al (2007) reported that soil amendment with plant residues inhibited plant growth in 119 of 1728 experiments (6.9%).…”
Section: Introductionmentioning
confidence: 99%
“…Many genera in the Agavaceae, of which Yucca is a member, abscise flowers after damage by insect feeding or oviposition (Sutherland 1987;Becerra & Lloyd 1992;Pellmyr 1997), despite not being associated with pollinating seed predators (see also Marr & Pellmyr 2003). Similarly, non-leguminous plants, which do not associate with rhizobia, respond to nitrogen soil availability via differential root investment, which would be a preadaptation for legume host sanctions if the trait occurs in the non-rhizobia-associated ancestors of legumes (Hodge et al 1998(Hodge et al , 1999Farley & Fitter 1999;Wijesinghe et al 2001). Thus, it is modularity that provides stronger evidence of adaptation.…”
Section: The Net Marginal Benefit Of Patrolling B(d) Ismentioning
confidence: 99%